Understanding Innovation Ecosystems: A Framework for Joint Analysis an d Action. Cambridge: MIT D-Lab - Hoffecker, Elizabeth (MIT D-Lab, 2019)
Place-based innovation ecosystems play a crucial role in driving local and regional economic development. This role has been documented and understood for over 40 years in industrialized economies but is only s tarting to be appreciated in the context of emerging and developing ec onomies. However, the past several years have seen an intensification of interest in innovation ecosystems among global development actors a s well as practitioners and policymakers working across the Global Sou th. Whether at the municipal level, in places such as Medellín, Colomb ia and Guadalajara, México, or the national level in Rwanda, South Afr ica, or India, we see governments, multi-laterals, donors, and civil s ociety actors embarking on initiatives to strengthen local innovation ecosystems. The International Development Innovation Alliance, for exa mple, which includes many of the largest public and private global dev elopment agencies, has created a set of recommendations for why and ho w actors investing in economic development should support the strength ening of innovation ecosystems. Within the past year, MIT D-Lab has be en invited to play a role in some of these ecosystem-strengthening eff orts. In contexts ranging from Oaxaca, México to Accra, Ghana, we have been asked to convene ecosystem actors and stakeholders in order to f acilitate joint ecosystem strengthening work. In preparing for these e ngagements, we have researched the state of the field regarding both i nnovation and entrepreneurial ecosystems as well as existing ecosystem frameworks, models, and tools. In doing so, it has become clear that much of the current thinking and practice related to these concepts is drawn from research on innovation processes and entrepreneurial clust ers in highly developed economies — places like Silicon Valley and Ken dall Square, Boston. Much less is known about innovation ecosystems in less-developed contexts in terms of how they can be characterized, ho w they function, and — most importantly — how they can be strengthened . To that end, the Local Innovation Group at D-Lab has been conducting multi-year research on local innovation ecosystems in the types of co ntexts where D-Lab and our partners engage. This involves learning abo ut diverse processes of ecosystem development through primary and seco ndary case study research. Based on this research, we have developed a framework for understanding local innovation ecosystems, which we sha re in this publication. We have found the framework, and accompanying visual model, to be a useful tool for orienting and organizing convers ations among ecosystem actors on how particular innovation ecosystems are functioning, what their strengths and weaknesses are, and where op portunities for further development might lie. This document shares th is framework and how we have used it over the past year to catalyze ec osystem-strengthening efforts. We start by clarifying the concept of a “local innovation ecosystem” and presenting the core ideas informing the visual model. We then describe the model and each of its individua l components. We follow with guidance from our research on best practi ces for conducting ecosystem strengthening work, and share three examp les of how we have used the model to facilitate ecosystem-strengthenin g conversations in distinct local contexts.